(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article examines the recent trends and issues in Indian federalism. The federal system has become transformedly in the last seven decades—from being dismissed as a full-fledged federal system to a widely acclaimed federal system in the world.